Innovative microelectronic technologies for high-energy physics experiments - Borshchov, V.M.; Listratenko, O.M.; Protsenko, M.A.; Tymchuk, I.T.; Fomin, O.O. (Functional Materials, 2017)
In the paper there are proposed new approaches to for creating the innovative design-technological solutions and manufacture technologies of advanced thin pixel array detector modules based on high resolution CMOS monolithic active pixel sensors as well as flexible adhesiveless aluminium-polyimide flexible boards and cables for high-energy physics experiments.